Effectiveness of PEDE Training for The Psychological Well-Being of Women - Neka Erlyani; Rika Vira Zwagery; Ayu Regina (Psikodimensia: Kajian Ilmiah Psikologi, 2023)
Every individual will experience various pleasant or unpleasant events, including women. One of unpleasant experience is domestic violence. Some forms of fear and stress experienced by victims will lead to behavior that can hinder their daily activities. For this reason, treatment needs to be carried out by helping them to have abilities and improving their quality of life through psychological well-being. PEDE (Forgiveness, Self-Efficacy and Empathy) training aims to improve the psychological well-being of women from an internal perspective through three main training elements. This research used a quasi-experiment method and non-randomized one group pre-test post-test design involving 30 women from Palam Village Banjarbaru. The research results show that PEDE training is effective in improving the psychological well-being of women in Palam Village. It is hoped that this training in forgiveness, self-efficacy and empathy can be applied in everyday life as a form of strengthening the family, and an effort to reduce the mental burden of the problems experienced so as to achieve the psychological well-being of women in the family.